EVALUATION OF NEUROMUSCULAR ACTIVATION OF LUMBAR AND CERVICAL EXTENSION MUSCLE OF CYCLISTS WITH AND WITHOUT PAIN DURING DIFFERENT POSTURES AND CADENCES. (Fiep Bulletin - online, 2015)
The posture adopted in cycling can to be related with presence of lumbar and cervical pain of individuals who have been practicing it, but few studies have been investigated a degree of muscular activity of this regions and of this modality. Thus, the aim of this study was estimate a neuromuscular activation pattern for lumbar and cervical muscles of cyclist with pain and without pain. EMG signals were recorded of 10 male cyclists, during test performed in ergometer bicycles electromagnetic, with constant load and with variations of position and cadence. Qualitatively, the results demonstrated higher neuromuscular activation of the individuals with pain than individuals without pain, independently of the position and of the cadence. However, It was not possible to establish a degree of muscular activity duo to the fact that such differences were no significant. The level of significance adopted was of 0,05.
Keywords: cycling; position; EMG.